Applying Citation Analysis to Evaluate the Research Contributions of Accounting Faculty and Doctoral Programs. - Brown, Lawrence D.; Gardner, John C. (The Accounting Review, 1985)
Abstract ABSTRACT: This study applies citation analysis to evaluate the research contributions of accounting faculties, doctoral programs, and individuals to contemporary accounting research (CAR). A research contribution is measured as CAR citations to a journal article written by an accountant, and CAR is defined as all main articles published in The Accounting Review, Journal of Accounting Research, Journal of Accounting and Economics, and Accounting, Organizations and Society between 1976 and 1982. The advantages and disadvantages of the technique are discussed, and the sensitivity of the results to alternative citation measurement metrics is examined.